Ibsen’s unfavourable opinions on Poland: ignorance or contempt? - Sokół, Lech (Folia Scandinavica Posnaniensia, 2007)
It was only three times that Henrik Ibsen voiced his opinions on Poland: her national character, history, culture and political future; twice in his letters to, respectively, Bj0rstjeme Bjømson of 28 January 1865 and Georg Brandes of 30 September 1888, and once in his poem Abraham Lincolns mord (The Murder of Abraham Lincoln), almost totally unknown in Poland. The opinions were brief and vague, besides, they were private, passed in personal letters. The mention in the poem was connected with bitter remarks regarding contemporary politics and hypocrisy o f the mighty political rulers of the world and false public opinion. Ibsen’s remarks were, in fact, part of his meditations on Norway, Scandinavia, Europe and only in this context were aimed at saying a few words about Poland, a country he never showed any interest in. They were interesting only in connection with his political and historical thinking. His opinions on Poland were far from being favourable but it would be difficult to consider them as malicious or hostile.